2021
DOI: 10.3390/ijms23010415
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Role of miR-149-5p in the Carcinogenesis

Abstract: miR-149 is an miRNA with essential roles in carcinogenesis. This miRNA is encoded by the MIR149 gene on 2q37.3. The miR-149 hairpin produces miR-149-5p and miR-149-3p, which are the “guide” and the sister “passenger” strands, respectively. Deep sequencing experiments have shown higher prevalence of miR-149-5p compared with miR-149-3p. Notably, both oncogenic and tumor suppressive roles have been reported for miR-149-5p. In this review, we summarize the impact of miR-149-5p in the tumorigenesis and elaborate me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Earlier studies indicate that miR-149-5p acts as a tumor suppressor and is downregulated in many human cancers. 16 For example, Wang et al reported that miR-149 is an independent prognostic factor for overall survival in CRC patients, and ectopic expression of miR-149-5p decreases tumor cell growth and invasion. 17 progression and metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies indicate that miR-149-5p acts as a tumor suppressor and is downregulated in many human cancers. 16 For example, Wang et al reported that miR-149 is an independent prognostic factor for overall survival in CRC patients, and ectopic expression of miR-149-5p decreases tumor cell growth and invasion. 17 progression and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the mechanism of action of circBGN, we searched for a potential target miRNA and identified miR‐149‐5p. Earlier studies indicate that miR‐149‐5p acts as a tumor suppressor and is downregulated in many human cancers 16 . For example, Wang et al reported that miR‐149 is an independent prognostic factor for overall survival in CRC patients, and ectopic expression of miR‐149‐5p decreases tumor cell growth and invasion 17 .…”
Section: Discussionmentioning
confidence: 99%
“…[5] miR-149 is a miRNA with essential roles in carcinogenesis, it is encoded by MIR149 gene on 2q37.3, the most appreciated mechanism of miR-149-5p dysregulation in cancer cells is the sequestering effects of these lncRNAs and circRNAs on it. [6] miR-149 was shown to inhibit tumor cell proliferation, migration, and invasion in renal cell carcinoma, bladder cancer, GC, and colorectal cancer. [7] Previous experiment in GC has shown miR-149 regulates metabolic pathways through AKT1/mTOR axis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, miR-149 has been shown to be tumor suppressor, the circCTNNA1/miR-149/FOXM1 axis has been suggested as a target for therapeutic interventions in colorectal cancer, miR-149-5p has also been shown to be sponged by other oncogenic noncoding RNAs such as PCAT1, DLGAP1-AS1, and circ5615 in colorectal cancer cells. [6] miRNA-149 was under-expressed in GC tissues and cells, while overexpression of miRNA-149 promoted cell apoptosis, retarded cell cycle, and inhibited proliferation and migration. [8] Several studies investigated the role of miR-149 polymorphisms in the development of GC, [9–16] but the results are conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…For many years the role of miRNA is mostly associated with translation arrest. miRNAs have crucial roles in the developmental processes and have various biological functions ( Fu et al, 2013 ; Ghafouri-Fard et al, 2021a ; Hussen et al, 2021 ). The process of miRNA synthesis contains multiple steps with the final step being incorporation of either the 5p or 3p strands of the mature miRNA duplex into a complex, namely miRNA-induced silencing complex (miRISC).…”
Section: Introductionmentioning
confidence: 99%